Describing the growth and rapid weight gain of urban Australian Aboriginal infants. Issue 4 (10th April 2013) - Webster, Vana; Denney‐Wilson, Elizabeth; Knight, Jennifer; Comino, Elizabeth; ,
Abstract : Aim: The aims of this paper are to describe the growth of urban Australian Aboriginal infants from birth to 24 months of age and to identify the proportion of these infants experiencing rapid weight gain (RWG) and overweight/obesity. Methods: The Gudaga Study is a longitudinal birth cohort of 159 Australian Aboriginal children born on the urban fringe of Sydney. Birthweight and length were extracted from hospital data. Children with a birthweight >1500 grams were included in the analysis ( n = 157). Weight, length and head circumference were measured at 2–3 weeks and then six‐monthly until 24 months of age. Age‐ and gender‐specific Z‐scores were determined from the Centers for Disease Control (CDC) 2000 growth charts for weight, length, head circumference and body mass index (BMI). The proportion of children experiencing RWG (an increase in weight‐for‐age Z‐scores ≥0.67 between birth and 12 months) was calculated. The association between RWG and ≥85th CDC percentile for BMI at 24 months was tested using Pearson's χ 2 . Results: The mean weight of Gudaga infants was less than the CDC mean length‐for‐age at birth and 2–3 weeks of age but greater than CDC mean length‐for‐age and weight‐for‐age at 18 and 24 months of age. Overall, 42 infants (34.4%) experienced RWG, and 45 infants (36.9%) were overweight/obese at 24 months of age. A greater proportion of those who experienced RWG (61.9%) were overweight/obese at 24 months than those who did not experience RWG (23.8%). Conclusion: Our study suggests a concerning proportion of urban Indigenous infants experience RWG and overweight/obesity in early childhood.